KCl-CaCO3 nanoclusters armoured with Pt nanocrystals for enhanced electro-driven tumor inhibition. (20th December 2021) - Chen, Tong; Fu, Yike; Zhang, Ruoyu; Han, Gaorong; Li, Xiang
Abstract : Nanoclusters, consisting of potassium chloride nanocrystals and amorphous calcium carbonate, were synthesized and integrated with platinum nanoparticles to enable the agitated electric-driven tumor inhibition. Abstract : Electrodynamic therapy (EDT) has recently emerged as an alternative approach for tumor therapy via the generation of ROS by platinum (Pt) nanoparticles under electric field. An interesting phenomenon observed during EDT is that the increased on-site concentration of chloride ions is highly beneficial for ROS generation and inhibition efficacy. Here, in this study, nanoclusters (KCC), consisting of potassium chloride (KCl) nanocrystals and amorphous calcium carbonate (CaCO3 ), were synthesized and integrated with platinum nanoparticles (KCCP). In this system, KCC can dissolve and release calcium and chloride ions within tumor cells. The intracellular chloride ions considerably facilitated ROS generation by Pt nanoparticles under an electric field. More importantly, the excessive calcium ions and ROS formed a cycle of mutual promotion and self-amplification in cells, leading to agitated tumor inhibition, both in vitro and in vivo .